ANALISIS KAPASITAS PRODUKSI KARET PETANI TERHADAP PEMENUHAN INPUT CRUMB RUBBER DI KABUPATEN KUANTAN SINGINGI - Nababan Warni Lincu; Isyandi Isyandi; Taryono Taryono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
Rubber is one of the agricultural commodities in Indonesia. This commodity has been cultivated relatively longer than other plantation commodities. The production and productivity of rubber plants does not always increase, sometimes there is a decrease, and the amount of production is constant. This is influenced by factors of production such as the number of workers, land area, capital, technology. This research was conducted in a rubber plantation in Kuantan Singingi Regency. The purpose of this study was to determine the rubber production capacity of farmers to fulfill the input of crumb rubber in Kuantan Singingi Regency and to determine the added value of rubber plants in Kuantan Singingi. This research uses primary data, namely by conducting interviews with farmers and PT Logas factory employees. The results show that rubber farmers in the logas area and outside the Kuantan Singingi area meet the Crumb Rubber Production capacity at PT Logas.Kewords:: Rubber, production capacity, value added